Anti-Angiogenic Potential of Marine Streptomyces-Derived Lucknolide A on VEGF/VEGFR2 Signaling in Human Endothelial Cells - Byeoung-Kyu Choi; Min-Hee Jo; Hee Jae Shin; Sun Joo Park (Molecules)
Angiogenesis, primarily driven by the vascular endothelial growth factor (VEGF) and its receptor, the VEGFR, plays a key role in various pathological processes such as cancer progression. Here, we investigated the anti-angiogenic effects of Lucknolide A (LA), a marine Streptomyces-derived compound, and evaluated its potential as a VEGFR2 inhibitor. LA selectively inhibited the proliferation of human endothelial cells EA.hy926 and HUVEC while exhibiting minimal effects on normal fibroblasts and various tumor cells. LA induced S-phase cell cycle arrest and apoptosis in EA.hy926 cells, increasing apoptotic markers p53, Bax, and p21 and decreasing the anti-apoptotic protein Bcl-2, with these effects being further enhanced under VEGF stimulation. Additionally, LA suppressed VEGFR2 phosphorylation and its downstream signaling pathways, including Akt/mTOR/p70S6K, MEK/ERK, Src, FAK, and p38 MAPK, which are crucial for endothelial survival and angiogenesis. Molecular docking studies revealed that LA binds to both inactive (DFG-out, PDB: 4ASD) and active (DFG-in, PDB: 3B8R) VEGFR2 conformations, with a significantly stronger affinity for the active state (−107.96 kcal/mol) than the inactive state (−33.56 kcal/mol), suggesting its potential as a VEGFR2 kinase inhibitor. Functionally, LA significantly inhibited VEGF-induced endothelial migration, tube formation, and microvessel sprouting in both in vitro and ex vivo rat aortic ring assays. Additionally, LA reduced tumor-associated tube formation induced by human breast tumor cells (MDA-MB-231), indicating its potential to suppress VEGF-dependent tumor angiogenesis. These findings suggest that LA is a promising selective anti-angiogenic agent with potential therapeutic applications in angiogenesis-related diseases such as cancer.